2007
DOI: 10.1159/000097970
|View full text |Cite
|
Sign up to set email alerts
|

Pain Response in Depersonalization: A Functional Imaging Study Using Hypnosis in Healthy Subjects

Abstract: Background: Depersonalization (DP) is characterized by persistent or recurrent episodes of detachment from one’s self with reduced pain perception being a common feature. Alterations in the body schema similar to the cortico-limbic disconnection syndrome of pain asymbolia are suggested to be responsible for DP. In this study we used hypnosis to induce DP in healthy subjects and to examine neural patterns of pain perception in the state of DP by means of functional magnetic resonance imaging (fMRI). Methods: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 81 publications
(58 reference statements)
1
38
0
3
Order By: Relevance
“…31,32 Röeder and colleagues 33 found reduced amygdala activity during induced depersonalization in healthy control participants. Taken together, these findings suggest that reduced temporal activity is a potential correlate of dissociation and reduced pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Röeder and colleagues 33 found reduced amygdala activity during induced depersonalization in healthy control participants. Taken together, these findings suggest that reduced temporal activity is a potential correlate of dissociation and reduced pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…60 Similar results were obtained during hypnosis-induced depersonalisation. 61 These studies revealed the neural correlates of different aspects of hypnotic analgesia. They showed ACC or somatosensory cortex to be suppressed, depending on the content of the hypnotic suggestions.…”
Section: Functional Neuroimaging and Psychotherapy Dej Lindenmentioning
confidence: 98%
“…Hypnosis can be used to reliably produce hallucinations in some highly suggestible individuals (Woody & Szechtman, 2011), thereby providing opportunities to study a phenomenon that is normally intractable within laboratory contexts (see also §5.2). In particular, researchers have used suggestion to induce auditory and visual hallucinations (Kosslyn, Thompson, Costantini-Ferrando, Alpert, & Spiegel, 2000;McGeown et al, 2012;Szechtman, Woody, Bowers, & Nahmias, 1998), as well as more complicated multimodal hallucinations (Nash, Lynn, & Stanley, 1984;Röder, Michal, Overbeck, van de Ven, & Linden, 2007). For example, one study found that suggestions for autoscopy (a visual hallucination of one's own body) coupled with a suggestion for disembodiment (the perception of being physically detached from one's body) was associated with reduced activation in right temporal parietal junction and medial prefrontal cortex relative to a control condition (Röder et al, 2007).…”
Section: Perceptionmentioning
confidence: 99%
“…In particular, researchers have used suggestion to induce auditory and visual hallucinations (Kosslyn, Thompson, Costantini-Ferrando, Alpert, & Spiegel, 2000;McGeown et al, 2012;Szechtman, Woody, Bowers, & Nahmias, 1998), as well as more complicated multimodal hallucinations (Nash, Lynn, & Stanley, 1984;Röder, Michal, Overbeck, van de Ven, & Linden, 2007). For example, one study found that suggestions for autoscopy (a visual hallucination of one's own body) coupled with a suggestion for disembodiment (the perception of being physically detached from one's body) was associated with reduced activation in right temporal parietal junction and medial prefrontal cortex relative to a control condition (Röder et al, 2007). This is notable because previous research has shown that direct electrical stimulation of right temporal parietal junction in an epilepsy patient reliably produced out-of-body experiences (Blanke, Ortigue, Landis, & Seeck, 2002); the latter result provides indirect corroboration of the neurophysiological effects of specific suggestions.…”
Section: Perceptionmentioning
confidence: 99%